STRATEGI PUBLIC RELATIONS KUSUMA SAHID PRINCE HOTEL SOLO DALAM MEMBENTUK CITRA DI TENGAH PANDEMI COVID 19 - Wulandari, Azalia Agnes (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2022)
The COVID-19 pandemic in Indonesia had a significant impact on the hotel sector. One of them is Kusuma Sahid Prince Hotel (KSPH) Solo. KSPH Solo requires the role of public relations to design a strategy in the covid 19 pandemic era. In addition, this strategy aims to restore public confidence to stay, visit, and hold events at KSPH Solo without feeling afraid, worried, and anxious. Public trust will form an opinion and behavior to build a good and positive image of Kusuma Sahid Prince Hotel Solo. This study aims to explain the public relations strategy of Kusuma Sahid Prince Hotel Solo in forming an image in the covid 19 pandemic era. This research is descriptive with qualitative methods. The data used the results of interviews with public relations KSPH Solo, Instagram screenshots of KSPH Solo, and observations to KSPH Solo. Furthermore, this study also used the results of questionnaires that were distributed to respondents. The sampling method is purposive sampling which includes data related to public relations and image strategies. In addition, the respondents are selected based on specific predetermined criteria. This study indicates that the planned public relations strategy of Kusuma Sahid Prince Hotel Solo can be carried out optimally even though there are many limitations in the covid 19 pandemic era, such as defining problems, planning and programming, taking action and communication, and evaluating programs. Therefore, the image formed through the questionnaire distributed to the respondents got the community's good and positive image towards Kusuma Sahid Prince Hotel Solo.